Measurement of Cationic Polyelectrolyte Concentration by Continuous Flow Collid Titration - IGARASHI, Chiaki (Japan journal of water pollution research, 1991)
Studies were made in which a continuous flow analysis was applied in colloid titration to measure cationic polyelectrolytes. For establishing the dosage at the end point of titration, a dual-frequency photometric cell was used. Effects caused by dissolved salinity and turbidity were also investigated. Results obtained were as follows. 1) It was possible to use the colloid titration end point as the set value, wherein a constant-fold value of the difference in the transmitted light intensity just before adding the titrant is defined as the titration end point, and whereby the transition reaction of a toluidine blue indicator is detected through the difference in the transmitted light intensity at each frequency subject to measurement. 2) It was possible to measure samples whose ionic strength was less than approximately 0.04 as they were not diluted, provided that the said constant was 0.8 and that the titration end point was defined as the region where the transition reaction of the indicator began. 3) The effect of turbidity on this measurement method could be neglected, provided that the turbidity of samples were below approximately 150 units. 4) The continuous flow analysis testing system were determined to have favorable responsibility and accuracy within a range of 00.1meq·l-1.